The American College of Sports Medicine (ACSM)
Homepage of the American College of Sports Medicine which promotes and integrates scientific research, education, and practical applications of sports medicine and exercise science to maintain and enhance physical performance, fitness, health, and quality of life. Content: About ACSM | Member Service Center | Certification & Career I Center | Media Room | Partners & Programs | Reference & Research I Library | Public Arena | ACSM International |